The Acute-Care Nurse Practitioner: A Transformational Journey - Judy Rashotte (Athabasca University Press, 2013)
The Acute-Care Nurse Practitioner is based on in-depth interviews with twenty-six nurse practitioners working in acute-care settings within tertiary-care institutions all across Canada. Employing a hermeneutic approach, Rashotte explores the perspectives from which NPs view their reality as they undergo a transformational journey of becoming a journey that is directed both outward, into the world, and inward, into the self. We learn how, in their struggle to engage in a meaningful practice that fulfills their goals as nurses, their purpose was hindered or achieved. In large part, the story unfolds in the voices of the NPs themselves, but their words are complemented by descriptive passages and excerpts of poetry that construct an animated and powerful commentary on their journey.